PROBLEMS OF ECONOMIC DEVELOPMENT OF SMALL BUSINESS IN THE REAL SECTOR - Sharipov Tulkin Saidakhmedovich; Ubaydullayev Bekhruz (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the current state of small business and private entrepreneurship in Uzbekistan, the problems of development and state support for small business and private entrepreneurship. On the basis of statistical data, conclusions are presented about the features of the development of small business and private entrepreneurship and measures to address them.